Problem based learning in leaching mathematics to foreign students - Chakrabarty, Sheila (2012)
Mathematics is a core subject for foundation students who will be taking up engineering, pharmacy, medicine and architecture. Therefore, it is crucial that a proper and effective method of teaching is adapted in order to build their understanding in mathematics. This paper discusses types of activities given based on problem based learning (PBL). 40 undergraduate foundation level foreign students participated in this study. These students come from diverse background especially in terms of culture and language. Communicating in English is a major problem amongst them. The researcher divided the students into small groups of 5 and presented 3 tasks in duration of 6 weeks. Topics covered were functions, matrix and trigonometry. They work in groups, discusses what to learn in order to solve the assign problem. They apply their new knowledge on the problem and reflect on what they learned and the effectiveness of the strategies employed. The teacher acts to facilitate the learning process rather than to provide knowledge. As the course progressed, they showed more confidence as they grew closer to each other and be able to grasp the content and apply their knowledge to solve the problems given to them. The findings show that there was an active participation on the students’ part and from the interview conducted; it was found that most of them gained more confidence and were able to communicate with each other towards a common goal despite their differences. They become more motivated to learn as they begun to solve problems. As such, problem based learning is an approach that can help develop students’ better understanding in mathematics as it enhances critical thinking , problem solving skills as well as communication skills. Hence, PBL can promote lifelong learning and is an effective approach in overcoming cultural barriers and encourages unity and collaborative learning within diverse student groups.